Delta life : exploring dynamic environments where rivers meet the sea - Krause, Franz; Harris, Mark, 1969 March 12- (Studies in environmental anthropology and ethnobiology ;, 2021)
"Proposing a series of innovative steps towards better understanding human lives at the interstices of water and land, this volume includes eight ethnographies from deltas around the world. The book presents 'delta life' with intimate descriptions of the predicaments, imaginations and activities of delta inhabitants. Conceptually, the collection develops 'delta life' as a metaphor for approaching continual and intersecting sociocultural, economic and material transformations more widely. The book revolves around questions of hydrosociality, volatility, rhythms and scale. It thereby yields insights into people's lives that conventional, hydrological approaches to deltas cannot provide"--